The Stackelberg game model of cross-border river flood control - Wang, Qiang; Bai, Yuntao; Yang, Yueling (Frontiers in Ecology and Evolution, 2022)
This paper, first of all, set up a separate management between upstream and downstream flooding, stark game model, and the establishment of a compensation management between upstream and downstream flooding stark's game model, and then established the joint governance between upstream and downstream flood resources of stark's game model, the Nash equilibrium under various conditions, finally has carried on the numerical analysis. The conclusion shows that when the flood control in the upstream area has a great impact on the downstream area, the flood control in the upstream area decreases gradually and the flood control in the downstream area increases gradually with the increase of flood control compensation. And when the compensation amount of flood control is greater than a certain value, the flood control of the downstream area will exceed that of the upstream area. Under the model of cooperative flood control, the amount of flood control in the upstream and downstream areas will be less than the amount of flood control in the upstream area alone, regardless of the proportion allocated to the upstream area. When flood control in upstream areas has a greater impact on downstream areas, social welfare in both upstream and downstream areas will increase first and then decrease. When the compensation amount of flood control is greater than a certain value, the social welfare of the downstream areas under the flood control compensation exists and the social welfare under the flood control resources alone. Under the model of cooperative water resources development, the social welfare of the upstream and downstream areas will be greater than that of the downstream areas in terms of flood resources management. With the increase of flood control compensation, the proportion of flood control development in the upstream and downstream regions gradually decreases. In the mode of cooperative water resources development, when the proportion of the distribution to the upstream area is greater than a certain value, the water resources developed and utilized by the upstream area under the mode of joint flood control is greater than that under the mode of single flood control.